Conformable Double Laplace–Sumudu Transform Decomposition Method for Fractional Partial Differential Equations - Jia Honggang; Zhao Yanmin (Complexity)
In this work, we proposed a new method called conformable fractional double Laplace–Sumudu transform decomposition method (CFDLSTDM) to solve fractional partial differential equations (FPDEs).This method is a combination of the Laplace–Sumudu transform method and the Adomian decomposition method. Besides, we presented some excellent properties and results of conformable double Laplace–Sumudu transform (CDLST). Illustrative examples results are given to show that the CFDLSTDM is an effective and accurate approach for fractional partial differential equations.